Kepemimpinan Manajerial Pengasuh Pondok Pesantren Al-Amin Sukaoneng Tambak - Istiqomah, Nurul (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2024)
This research aims to determine the leadership role of Kyai in managing Islamic boarding schools in the Al-Amin Sukaoneng Islamic Boarding School environment in improving the discipline of students. This research uses descriptive qualitative methods. The researchers used data collection by means of interviews, observation and documentation. The main data source for this research consisted of 4 people, namely Islamic Boarding School Teachers, Ustadz, Islamic Boarding School Management and Students. To check the validity of the data, the researcher used the triangulation method for data from field results. The role of the Kyai in managing the Islamic Boarding School to increase community diversity consists of (1) the Kyai's advice as a spirit in increasing diversity (2) the relationship between the Islamic Boarding School and the Community in increasing the diversity of social relations between Santri, Kyai and the Community, (3) Kyai as the guardian of Indonesian Islamic traditions . In this way, the governance of Islamic boarding schools will be better in terms of education policy, especially in responding to the development of Islamic social movements which continue to grow day by day.